The ERGONOMIC ANALYSIS MARAS BETON WORKERS TO MINIMIZE LOW BACK PAIN USING THE RECOMMENDED WEGHT LIMIT (RWL) METHOD: ANALISIS ERGONOMI PADA PEKERJA CV. MARAS BETON UNTUK MEMINIMALISIR LOW BACK PAIN MENGGUNAKAN METODE RECOMMENDED WEGHT LIMIT (RWL) - Nurul Hudaningsih; Ashabul Ababekar (Hexagon, 2025)
CV Maras Beton is one of the paving block producers in Sumbawa Regency. Some work activities at CV Maras Beton use machines, but some use employees' physical strength. It was found from interviews with workers that several workers who handled physical work activities experienced pain in the shoulders, thighs, waist, and legs. Namely the work of lifting sand, removing stone ash, lifting dry paving blocks, and lifting paving blocks from the machine to the hand pallet. Therefore, an ergonomic analysis was conducted on these workers to minimize work-related illnesses, including low back pain. This research uses a biomechanical approach with the Recommended Weight Limit (RWL) method. Based on the research results, it was concluded that there was one job that was categorized as high risk, namely the sand removal process. Another job categorized as medium risk is lifting paving blocks from the machine to the hand pallet. Two other jobs, namely removing stone ash and removing dry paving blocks, are categorized as low risk. So the work that requires urgent repairs is sand removal activities.